Metabolic alterations derived from absence of Two-Pore Channel 1 at cardiac level. - Garcia-Rua, V; Feijoo-Bandin, S; Garcia-Vence, M; Aragon-Herrera, A; Bravo, S; Rodriguez-Penas, D; Mosquera-Leal, A; Lear, P; Parrington, J; Alonso, J; Rosello-Lleti, E; Portoles, M; et al. (Springer, 2016)
Two-pore channels (TPCs or TPCNs) are novel voltage-gated ion channels that have been postulated to act as Ca2+ and/or Na+ channels expressed exclusively in acidic organelles such as endosomes and lysosomes. TPCNs participate in the regulation of diverse biological processes and recently have been proposed to be involved in the pathophysiology of metabolic disorders such as obesity, fatty liver disease and type 2 diabetes mellitus. Due to the importance of these pathologies in the development of cardiovascular diseases, we aimed to study the possible role of two-pore channel 1 (TPCN1) in the regulation of cardiac metabolism. To explore the cardiac function of TPCN1, we developed proteomic approaches as 2-DE-MALDI-MS and LC-MALDI-MS in the cardiac left ventricle of TPCN1 KO and WT mice, and found alterations in several proteins implicated in glucose and fatty acid metabolism in TPCN1 KO vs. WT mice. The results confirmed the altered expression of HFABP, a key fatty acid transport protein, and of enolase and PGK1, the key enzymes in the glycolytic process. Finally, in vitro experiments performed in neonatal rat cardiomyocytes, in which TPCN1 was silenced using siRNAs, confirmed that the downregulation of TPCN1 gene expression increased 2-deoxy-D-[3H]-glucose uptake and GLUT4 mobilization into cell peripherals in cardiac cells. Our results are the first to suggest a potential role for TPCNs in cardiac metabolism regulation.